Cultural Muslims: Popular Religiosity among Teachers in Public Elementary Schools in Turkey - YILMAZ, Selman (Journal of History Culture and Art Research, 2013)
Abstract Even though there are many studies about religious life in Turkey, there are very few that examine religiosity within a specific profession. This study explores popular religiosity among Turkish elementary school teachers. Popular religion, folk religion, unofficial religion, invisible religion, common religion, religious populism”all of these terms point to a dimension of religious life that suggests a differentiation between the religion of ordinary people and the religion of theologians, reverends, and other religious professionals. In this study, I use the results of a survey that I conducted with 295 teachers in 12 public elementary schools in Turkey in 2005 to explore popular religiosity among teachers. The results show that popular religiosity is lower among teachers than the majority of population. However, some teachers make religion a part of their cultural life, and see the practice of religion as a cultural habit.